Design and Specific Absorption Rate of 2.6 GHz Rectangular-Shaped Planar Inverted-F Antenna - Nurul Inshirah Mohd Razali; Norhudah Seman; Nur Ilham Aliyaa Ishak (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This article presents the investigation of specific absorption rate (SAR) of a rectangular-shaped planar inverted-F antenna (PIFA) at frequency of 2.6 GHz. Initially, the design antenna is presented with parametric study concerning the dimensions of antenna patch length, shorting plate, ground plane and substrate. The proposed PIFA antenna has -20.46 dB reflection coefficient and 2.383 dB gain. The PIFA’s SAR is correlated with the antenna gain and excitation power. The analysis shows that higher gain contributes to a lower SAR value. While, the higher excitation power causes a higher SAR value. All the design and analysis are performed using the CST Microwave Studio